Autonomy in vocabulary learning: vocabulary learning strategies teaching programme for EFL Libyan learners - Khalifa, Salma H. M.; Shabdin, Ahmad Affendi (Arab Society of English Language Studies (ASELS), 2016)
Can learner autonomy be promoted through programmed teaching? To answer this question, a model of teaching vocabulary learning strategies programme, designed to help English as a Foreign Language (EFL) learners acquire autonomy in vocabulary learning, was developed and tested through an experimental study conducted at a secondary school in Libya. The present paper discusses the results obtained from the study. The data was collected through pre-test/post-test, logbooks. The participating students were divided into two groups: experimental group and control group. The experimental group students were taught new English vocabulary items along with teaching them the methods to enrich them further on their own, while the control group students were taught only new vocabulary items.Comparison of pre-test and post-test results showed that experimental group participants made considerable progress in achieving autonomy in vocabulary learning. The results obtained are highly significant in Libyan contexts where English is taught as a foreign language and students largely depend on classroom teaching and teachers' support, which create problems for them in university level education. The findings of the study indicate that (i) learner autonomy can be induced; and (ii) autonomous learners acquire new vocabulary faster. The study was conducted at a small scale.The researcher suggests that if the same study is conducted at a larger scale, the results will hold better validity.